(untitled) (Academicia Globe: Inderscience Research, 2023)
A leader must meet a number of requirements. The word "leadership" is given various meanings in explanatory dictionaries, such as management, advice, monitoring, direction, and instruction. It can be seen that there are many requirements that managers (leaders) need to meet in the current era. The need to develop management culture for the leader to succeed in management, the culture of management employees depends on many factors, the level of general culture, business qualities, deep and comprehensive knowledge of management science and having the ability to apply it in the course of their activities presented in this article.